Relationship Between Trace Element Content in the Brain of Bony Fish Species and Their Food Items in the Southwest of the Caspian Sea Due to Anthropogenic Activities - Masoud Sattari; Mohammad Forouhar Vajargah; Mehdi Bibak; Shima Bakhshalizadeh (Hamadan University of Medical Sciences, 2020)
The trace elements (TEs) in aquatic environments due to anthropogenic activities are readily available to aquatic organisms. There are 153 fish species inhabiting the Caspian Sea. However, little is known about TE (TE) concentrations in these species. In this study, we investigated the effects of TEs levels in the brain of some bony fish species inhabiting the Caspian basin. Totally, 405 fish from nine species with different feeding behaviors including Leuciscus aspius (n = 20) and Perca fluviatilis (n = 37) as piscivores, Rutilus kutum (n = 27) and Rutilus caspius (n = 71) as carnivores, Vimba persa (n = 56), Ponticola caspia (n = 25) and Tinca tinca (n = 31) as mollusivores, and Alburnus chalcoides (n = 77) and Alosa braschnikowi (n = 61) as zooplanktivores were collected from the southwest of the Caspian Sea basin from September 2017 to June 2018. The ICP-OES was used to measure TEs in the brain tissue of fish. The variability of TEs concentrations in the brain tissues of these fishes by principal component analysis (PCA) was decreased to 63.59% and 17.68% for PC1 and PC2, respectively, exhibiting that 81.27% of the total variability is associated with K, Mg, P, S, Zn, and Al. The two-dimensional diagrams showed the weight of each component in PCA. The PC1 was mostly influenced by P, Mg, K, and Zn, while the greatest value in PC2 belonged to Al. Furthermore, the entire number of elements determined in this study was found to be a suitable indicator for the distinction between fish species based on their feeding items.